Coagulation and fibrinolysis in injured patients - Innes, D. (1964)
Serial changes in coagulation and fibrinolysis studied among 42 patients admitted to hospital with a wide variety of injuries are reported. The first hours after trauma are dominated by an acceleration of fibrinolysis (clot lysis) and clotting time which are often followed by an abrupt rebound to prolonged fibrinolysis and normal clotting. Evidence is presented that acceleration of fibrinolysis is due to flooding of the circulation by plasminogen activator and that prolongation is probably due to an inhibitor. A prolonged prothrombin time, increased prothrombin consumption index, an acceleration of the heparin-retarded clotting time, and a fall in the platelet count are also frequent during the first hours after injury. There is evidence also of an early deficiency in factor V and the onset of a fall in factor VII and prothrombin. The following days are characterized by continued prolongation of fibrinolysis, a lengthening of clotting time, and an increased prothrombin consumption index suggestive of a defect in thrombo-plastin generation. Subsequent periods of prolonged fibrinolysis may develop. Prothrombin time often continues prolonged for one to three weeks and may vary phasically; plasma prothrombin and factor VII are reduced but there is now little change in factor V. The platelet count continues to fall for one to three days, then a thrombocytosis develops, often with abnormally high platelet levels, a week or so later. Plasma fibrinogen rises within 24 hours to reach a plateau maximum a few days later and levels remain high for prolonged periods in the severely injured. Various changes are related to or influenced by the severity of trauma. Mechanisms are discussed, including thrombosis in vivo, and reference is made to homeostatic significance and its possible breakdown.